Protection of Minor Labour in Bulgarian Legislation - Koycheva, Rayna (Research Papers, 2021)
In this article the author examines the protection of minor labour in Bulgarian legislation, distinguishes between the concepts of “child labor” and “minor labour”, outlines theoretically the conditions under which the minor labour is socially acceptable and analyzes the extent to which these conditions are observed in the Bulgarian legislation. As a result, it is concluded that the Bulgarian legislation meets international standards, providing a high level of protection of minor labour. However, the author makes some proposals de lege ferenda for additional measures which may contribute to an even higher level of this protection.
Keywords: Child labor; Protection of minor labour; Bulgarian legislation